Group-Specific Primer and Probe Sets to Detect Methanogenic Communities Using Quantitative Real-Time Polymerase Chain Reaction - Yu, Y.; Lee, C.; Kim, J.; Hwang, S.
Real-time polymerase chain reaction (PCR)is a highly sensitive method that can be used for the detection and quantification of microbial populations without cultivating them in anaerobic processes and environmental samples. This work was conducted to design primer and probe sets for the detection of methanogens using a real-time PCR with the TaqMan system. Six group-specific methanogenic primer and probe sets were designed. These sets separately detect four orders (Methanococcales, Methanobacteriales, Methanomicrobiales, and Methanosarcinales)along with two families (Methanosarcinaceae and Methanosaetaceae)of the order Methanosarcinales. We also designed the universal primer and probe sets that specifically detect the 16S rDNA of prokaryotes and of the domain Bacteria and Archaea, and which are fully compatible with the TaqMan real-time PCR system. Target-group specificity of each primer and probe set was empirically verified by testing DNA isolated from 28 archaeal cultures and by analyzing potential false results. In general, each primer and probe set was very specific to the target group. The primer and probe sets designed in this study can be used to detect and quantify the order-level (family-level in the case of Methanosarcinales)methanogenic groups in anaerobic biological processes and various environments.
Keywords: ANAEROBIC DIGESTION; METHANOGEN; MICROBIAL COMMUNITY; PRIMER AND PROBE SET; REAL-TIME QUANTITATIVE POLYMERASE CHAIN REACTION